Identification of critical molecular pathways involved in exosome-mediated improvement of cardiac function in a mouse model of muscular dystrophy - Su Xuan; Shen Yan; Jin Yue; Weintraub Neal L; Tang Yao-liang (Acta Pharmacologica Sinica, 2021)
Duchenne muscular dystrophy (DMD) is a progressive disease characterized by skeletal muscle atrophy, respiratory failure, and cardiomyopathy. Our previous studies have shown that transplantation with allogeneic myogenic progenitor-derived exosomes (MPC-Exo) can improve cardiac function in X-linked muscular dystrophy (Mdx) mice. In the present study we explored the molecular mechanisms underlying this beneficial effect. We quantified gene expression in the hearts of two strains of Mdx mice (D2.B10- DmdMdx/J and Utrntm1Ked-DmdMdx/J). Two days after MPC-Exo or control treatment, we performed unbiased next-generation RNA- sequencing to identify differentially expressed genes (DEGs) in treated Mdx hearts. Venn diagrams show a set of 780 genes that were ≥2-fold upregulated, and a set of 878 genes that were ≥2-fold downregulated, in both Mdx strains following MPC-Exo treatment as compared with control. Gene ontology (GO) and protein-protein interaction (PPI) network analysis showed that these DEGs were involved in a variety of physiological processes and pathways with a complex connection. qRT-PCR was performed to verify the upregulated ATP2B4 and Bcl-2 expression, and downregulated IL-6, MAPK8 and Wnt5a expression in MPC-Exo-treated Mdx hearts. Western blot analysis verified the increased level of Bcl-2 and decreased level of IL-6 protein in MPC-Exo-treated Mdx hearts compared with control treatment, suggesting that anti-apoptotic and anti-inflammatory effects might be responsible for heart function improvement by MPC-Exo. Based on these findings, we believed that these DEGs might be therapeutic targets that can be explored to develop new strategies for treating DMD.